Effect of Curcumin-containing Nanofibrous Gelatin-hydroxyapatite Scaffold on Proliferation and Early Osteogenic Differentiation of Dental Pulp Stem Cells - Dizaj, Solmaz M.; Rezaei, Yashar; Namaki, Fatemeh; Sharifi, Simin; Abdolahinia, Elaheh Dalir (Pharmaceutical Nanotechnology, 2024)
Background: In recent years, the electrospinning method has received attention because of its usage in producing a mimetic nanocomposite scaffold for tissue regeneration. Hydroxyapatite and gelatin are suitable materials for producing scaffolds, and curcumin has the osteogenesis induction effect. Aims: This study aimed to evaluate the toxicity and early osteogenic differentiation stimulation of nanofibrous gelatin-hydroxyapatite scaffold containing curcumin on dental pulp stem cells (DPSCs). Objective: The objective of the present investigation was the evaluation of the proliferative effect and primary osteogenic stimulation of DPSCs with a nanofibrous gelatin-hydroxyapatite scaffold containing curcumin. Hydroxyapatite and gelatin were used as suitable and biocompatible materials to make a scaffold suitable for stimulating osteogenesis. Curcumin was added to the scaffold as an osteogenic differentiation- enhancing agent. Methods: The effect of nano-scaffold on the proliferation of DPSCs was evaluated. The activity of alkaline phosphatase (ALP) as the early osteogenic marker was considered to assess primary osteogenesis stimulation in DPSCs. Results: The nanofibrous gelatin-hydroxyapatite scaffold containing curcumin significantly increased the proliferation and the ALP activity of DPSCs (P<0.05). The proliferative effect was insignificant in the first 2 days, but the scaffold increased cell proliferation by more than 40% in the fourth and sixth days. The prepared scaffold increased the activity of the ALP of DPSCs by 60% compared with the control after 14 days (p<0.05). Conclusion: The produced nanofibrous gelatin-hydroxyapatite scaffold containing curcumin can be utilized as a potential candidate in tissue engineering and regeneration of bone and tooth. Future Prospects: The prepared scaffold in the present study could be a beneficial biomaterial for tissue engineering and the regeneration of bone and tooth soon.
Keywords: scaffold